Trap column-based intact mass spectrometry for rapid and accurate evaluation of protein molecular weight. Issue 25 (24th May 2022) - Lim, Gyu-Min; Kim, Byung-Gee; Jeong, Hee-Jin
Abstract : Trap column-based intact mass spectrometry for estimating the molecular weight of proteins. Abstract : The determination of the molecular weight (MW) of a protein using high-resolution mass spectrometry (MS) is a crucial tool used to confirm whether the protein was correctly expressed and adequately purified. However, a non-volatile buffer is normally used for protein purification and storage. Therefore, a pre-treatment step using ultrafiltration (UF) is required to exchange the buffer with a volatile buffer prior to the introduction of the protein sample into the MS equipment. This pre-treatment step is time-consuming. In this study, a trap column-based pre-treatment method applied in a nano-LC system was developed for rapid and convenient analysis of the MW of proteins. First, the trap column system was compared with the conventional UF treatment system and non-treatment system using bovine serum albumin. Subsequently, the trap column system was applied to analyze the MW of commercially available and lab-synthesized recombinant proteins. The intensity of the base peak and signal-to-noise ratio of the trap column-based pre-treated protein were higher than those of the UF-treated protein. Moreover, the entire automated procedure of the trap column-based system was conducted within 20 min, which confirms its use in versatile and accurate protein identification.